Positive Gerechtigkeitspflichten gegenüber Flüchtenden - Paulmann, Franziska (2023)
This book deals with the philosophical question of what forms of justice exist to which refugees are entitled, especially in Western democracies. For this purpose, it first addresses the discussion of positive forms of such justice in general, in order to examine the case of refugees on this basis. To this end, the discussion is extended to examine the relevant collective agents such as nation states or the EU. Finally, this book critically examines the possible limitations of governments’ duty to provide justice to refugees based on the criteria of objective needs, competence, admissibility, reasonableness and the prospect of success.